2020
DOI: 10.1038/s41467-019-13774-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorinated hybrid solid-electrolyte-interphase for dendrite-free lithium deposition

Abstract: Lithium metal anodes have attracted extensive attention owing to their high theoretical specific capacity. However, the notorious reactivity of lithium prevents their practical applications, as evidenced by the undesired lithium dendrite growth and unstable solid electrolyte interphase formation. Here, we develop a facile, cost-effective and one-step approach to create an artificial lithium metal/electrolyte interphase by treating the lithium anode with a tin-containing electrolyte. As a result, an artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
237
0
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 367 publications
(241 citation statements)
references
References 69 publications
(105 reference statements)
3
237
0
1
Order By: Relevance
“…The impedance spectra were fitted using an equivalent circuit model in the inset of Figure 4e to estimate the values of R SEI and R ct . [ 11b ] The fitted values of R SEI and R ct were presented in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The impedance spectra were fitted using an equivalent circuit model in the inset of Figure 4e to estimate the values of R SEI and R ct . [ 11b ] The fitted values of R SEI and R ct were presented in Table S1 (Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…[ 9 ] In particular, physical protective layers have been intensively explored as one of artificial SEI layers to stabilize Li metal. Various physical protective layers were prepared using organic polymers, [ 10 ] inorganic materials, [ 11 ] and their mixture forms, such as composite protective layers. [ 12 ] In the case of composite protective layers, electrochemically inactive ZrO 2 , [ 12a ] LiF, [ 12b ] and Al 2 O 3 [ 12c ] were conventionally used as inorganic fillers to improve the mechanical strength of protective layers.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in R ct is due to possible side reactions at the interface that destroy the Li metal and SPE, and lead to the formation of unstable SEI. [41,58,59] When Li 2 S existed in the SPE, the R ct was smaller than that of the pure PEO-LiTFSI electrolyte both before and after circulation, which originated from the improved solid-solid interfacial contact, the effective control of side reactions, and the stabilized LiF-rich SEI. [60,61] In addition, the R ct of PEO-LiTFSI-Li 2 S batteries gradually increased in the initial cycles (190 Ω for 10 cycles) and declined in the following cycles (Figure 7f).…”
Section: The Application Of Solid Polymer Electrolytes (Spes) Is Stilmentioning
confidence: 99%
“…The following decrease of R ct can be contributed to high ion conductivity, low diffusion barrier, and high surface energy of LiF-rich interface, which can allow sufficient Li + transport and decrease the R ct . [58,62,63] In general, the strategy of introducing Li 2 S can effectively engineer the stable interface and boost the performance of electrochemical operation. The obviously improved performances of PEO-LiTFSI-Li 2 S based battery were attributed to the favorable interfacial stability of Li/PEO in battery.…”
Section: The Application Of Solid Polymer Electrolytes (Spes) Is Stilmentioning
confidence: 99%
“…In addition, by controlling gas pressure and reaction temperature, the LiF film with a controllable thickness can be achieved. Recently, Pathak et al (2020) have reported an artificial SEI composed of LiF, Sn, and the Sn-Li alloy with the thickness of 25 µm on the Li surface by treating the Li metal with a SnF 2 -containing electrolyte. This hybrid SEI layer facilitates the Li ion diffusion and Li storage via FIGURE 2 | (A) Schematic diagram of lithium surface with a pinhole-free and tightly connected Li 3 N film , adapted with permission from American Chemical Society (B) Schematic diagram and synthesis process of lithiophilic-lithiophobic gradient CNT interfacial layer (Zhang et al, 2018), adapted with permission from Nature Publishing Group.…”
Section: Ex-situ Inorganic Seimentioning
confidence: 99%